Chemical Engineering Education and Practice in Bangladesh (Journal of Chemical Engineering, 2012)
Chemical Engineering as a distinct engineering discipline is now more than hundred years old. It was 1888 when Professor Louis Mills Norton first introduced the curricula for Chemical Engineering at MIT. As creative chemists came up with new chemicals it provided ever new challenges to the Chemical Engineers to innovate new industrial processes applying the new found knowledge in unit operations, unit processes, reaction engineering, process control, (later) transport phenomena and (recently) process integration. In Bangladesh the founding fathers of engineering education took a long term view of the industrial development prospects and took the innovative decision to introduce Chemical Engineering curricula in the erstwhile Ahsanullah Engineering College in the early fifties. During these early years large corporations in the public sector provided the initial thrust for development of chemical and process industries. However it was not adequately appreciated during the formative years that mere experience in the successful operation of complex chemical plants does not constitute technology transfer in the real sense of the term. Professional in the field stressed the need for setting up of design sections where local chemical engineers with inputs form relevant professionals would be able to contribute meaningfully in establishing the design criteria for a plant. In the private sector Chemical Engineers have demonstrated in Bangladesh that they can be innovative in transferring technology and developing Ceramic and medium scale Basic Chemical industries. Thus, it has been amply demonstrated that accumulating technological capacity through such dynamic technology transfer efforts should be one of the avowed objectives of any development process. Professional Capability and Areas of Competence of Chemical Engineers have grown over the years in this country and this issue has been elaborated with specific examples.DOI: http://dx.doi.org/10.3329/jce.v26i1.10174 JCE 2011; 26(1): 1-8